Endogenous innovations in a model of the firm: Theory and empirical application for West-German manufacturing firms - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1997)
In the paper, a theoretical model of the determinants of innovation behaviour and investment is developed. The model is estimated with micro-data for West- German manufacturing firms from the ifo firm panel. The empirical results reveal a positive effect from firm size and market power on innovations. In addition, innovations depend positively on others innovations which indicates positive spillover effects. Finally, innovations depend positively on measures of excess demand at the firm level. This implies that temporary demand shocks affect output and productivity in the short run and in the long run! This underlines the importance of financing constraints for innovations and the complementarity of innovations and investment.
Keywords: D21; O31; 330; Endogenous innovations; market structure